Management of Giant Cell Tumor by Curettage and Bone graft in Weight Bearing Bone - A Study Done in CENTRAL MEDICAL COLLEGE. - Hamid, Md Kawser; Hasan, Md Mainul; Rahaman, Md Arifur; Hoque, Mohammad Emdadul; Patwary, Md Safiqur Rahman; Rahman, Minhazur (Central Medical College Journal, 2024)
Background: Giant cell tumor of bone (GCT) has been characterized as benign but often locally aggressive neoplasm that commonly occurs in proximity to weight bearing bone. Management of giant cell tumor of bone by curettage and bone graft in weight bearing bone is an effective method. This prospective experimental study was conducted among the patients with histologically proved giant-cell tumor who were admitted in the Department of orthopedic surgery, Central Medical College Hospital over a period of 18 months from January 2018 to June 2020. A total of 12 consecutive patients with histologically proved giant-cell tumour were included in the study. Majority (55.6%) of patient was in 3rd decade and male female ratio was 1:1.3. More than one fourth (25%) of the patients had GCT in the lower end of right femur, 33.3% in lower end of left femur, 25% in upper end of tibia, 16.7% in lower end of tibia and all patients had painful gait and swelling. According to campanacci grading, Grade-2 was found in all patients, and giant cell tumor was found in all patients, as evaluated by pre-operative biopsy. Cosmetically near normal appearance was found in 88.9% and 88.9% were able to do normal daily work. According to Schatzker and Lamber (1979) criteria excellent outcome was found in 41.7%, good in 50%, fair in 8.3%. Surgery in the form of intralesional curettage and filling the cavity with bone graft resulted in excellent relief of pain, cosmetically near normal appearance and patients were able to do normal daily work. Central Medical College Journal Vol 7 No 1 January 2023 Page: 7-12